Do targets of ostracism truthfully communicate their emotional reactions to sources? - Erdem O. Meral; Dongning Ren; Yvette van Osch; Eric van Dijk; Ilja van Beest (Acta Psychologica, 2023)
Ostracism triggers negative emotions such as sadness, anger, and hurt feelings. Do targets of ostracism truthfully share their emotions with the sources of ostracism? Drawing on past research on social-functional accounts of emotions and interpersonal emotion regulation, we investigated the possibility that targets may misrepresent their emotions (i.e., gaming emotions). We conducted three experiments (N = 1058; two pre-registered) using an online ball-tossing game, in which participants were randomly assigned to be included or ostracized. Consistent with the literature, we found that ostracized individuals were more hurt, sad, and angry than included individuals. However, we found little and inconsistent evidence that ostracized (vs included) individuals misrepresented their emotional reactions to the sources. Further, Bayesian analyses offered more support against misrepresentation of emotions. These findings suggest that targets of ostracism truthfully communicated their social pain to the sources.